2017
DOI: 10.7150/jca.19691
|View full text |Cite
|
Sign up to set email alerts
|

The Putative Role of TP53 Alterations and p53 Expression in Borderline Ovarian Tumors - Correlation with Clinicopathological Features and Prognosis: A Mini-Review

Abstract: Borderline ovarian tumors (BOTs) represent an independent group among ovarian malignancies, being diagnosed at clinical stage earlier than invasive ovarian carcinomas (OCs) and characterized by a rather favorable outcome after careful surgical management. Data published worldwide showed a substantial discordance of p53 expression in BOTs. The purpose of this work was to present the current status of knowledge on the significance of TP53 gene and p53 protein product alterations in BOTs. In general, higher p53 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 87 publications
1
5
0
1
Order By: Relevance
“…The role of p53 protein was described in carcinoma stem cells but little is known about p53 protein phosphorylation at serine 20 in CSCs biological behavior [11,12,14,15]. Similarly to earlier published data, we found that p53 nuclear accumulation was associated with worse clinical features of ovarian cancers [20][21][22][23][24][25][26]. p53 protein phosphorylation was analyzed very rarely in ovarian carcinomas and there are no data on its expression in ovarian carcinoma stem cells [27,28].…”
Section: Discussionsupporting
confidence: 80%
“…The role of p53 protein was described in carcinoma stem cells but little is known about p53 protein phosphorylation at serine 20 in CSCs biological behavior [11,12,14,15]. Similarly to earlier published data, we found that p53 nuclear accumulation was associated with worse clinical features of ovarian cancers [20][21][22][23][24][25][26]. p53 protein phosphorylation was analyzed very rarely in ovarian carcinomas and there are no data on its expression in ovarian carcinoma stem cells [27,28].…”
Section: Discussionsupporting
confidence: 80%
“…Particularly, we found that TP53 alterations were prominently associated with mutations in m1A-related regulatory genes. TP53 is a common tumour suppressor gene mutated in cancers, and the tumour suppressor protein p53 encoded by TP53 is usually absent in a variety of tumour types [29][30][31] . Previous studies have shown that TP53 mutations are prognosticators of poor outcomes in HCC 32 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 52 ] Multiple studies have revealed a correlation between p53 function and OC stem cells; however, evidence on a prognostic association between TP53 status and S100 family members in OC remains to be clarified. [ 53 ] In our current analysis, we found that the mRNA expression levels of S100A11, S100A14, and S100A16 were significantly increased, and increased S100A11, S100A14, S100A16, S100G, and S100P expression in TP53-mutated and S100A8, S100A11, and S100B expression in TP53-wild-type OC patients were correlated with poor OS, indicating that mutations in TP53 might regulate these S100 family members’ expression and participation in the development and progression of OC.…”
Section: Discussionmentioning
confidence: 70%